2005
DOI: 10.1007/s10681-005-5891-7
|View full text |Cite
|
Sign up to set email alerts
|

Identifying flavour targets for fruit breeding: A kiwifruit example

Abstract: The current study illustrates that fruit breeding should not only target elite fruit that are significantly more liked than existing cultivars, but also target special unique fruit that create major new flavour niches. Breeding targets can be identified in terms of consumer preferences for new and defined flavours. A trained panel was used to assess the flavours of a wide range of kiwifruit, and these characteristics were systematically arranged into flavour and odour wheels. These wheels describe some of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 22 publications
(23 reference statements)
0
31
0
Order By: Relevance
“…Each respondent was also asked to rank his/her preference among five types of fruit commonly sold in Oman (date, banana, mango, orange, apple), and to identify the critical eating quality attributes which influence his/her preference for each type of fruit. Fruit quality attributes listed in the questionnaire (size, colour, sweetness, firmness, flavour) were selected based on evidence in the literature on consumer attitudes and acceptability of a wide of fruit types (Alavoine et al 1990;Lockshin & Rhodus 1991;Kilcast & Fillion 2001;Crisosto et al 2003;Harker et al 2003aHarker et al , 2005Wismer et al 2005). In the third and last part of the questionnaire, respondents was asked to choose from a list the most common quality problems they observe in the market when selecting each type of fruit, and to choose a range of premium prices (0%, 1-10%, 11-25%, 26-50%, and >51%) that he/she was willing to pay for guarantee on superior quality fruit.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each respondent was also asked to rank his/her preference among five types of fruit commonly sold in Oman (date, banana, mango, orange, apple), and to identify the critical eating quality attributes which influence his/her preference for each type of fruit. Fruit quality attributes listed in the questionnaire (size, colour, sweetness, firmness, flavour) were selected based on evidence in the literature on consumer attitudes and acceptability of a wide of fruit types (Alavoine et al 1990;Lockshin & Rhodus 1991;Kilcast & Fillion 2001;Crisosto et al 2003;Harker et al 2003aHarker et al , 2005Wismer et al 2005). In the third and last part of the questionnaire, respondents was asked to choose from a list the most common quality problems they observe in the market when selecting each type of fruit, and to choose a range of premium prices (0%, 1-10%, 11-25%, 26-50%, and >51%) that he/she was willing to pay for guarantee on superior quality fruit.…”
Section: Methodsmentioning
confidence: 99%
“…Understanding those quality attributes that are important to the consumer is also useful in breeding research, to improve fruit quality and acceptability as well as in market-oriented fruit production (Wismer et al 2005). For instance, indepth studies have shown that consumers like apples (Malus domestica Borkh.)…”
Section: Introductionmentioning
confidence: 99%
“…Similar emphasis on developing unique shapes, colors, and fl avors is seen in other fruits. Examples of this would be a range of colors and fl avors among seedless table grapes, development of bright yellow-and red-fl eshed plums (Halgryn et al 2000 ) , work toward developing red-fl eshed apples (Volz et al 2009a, b ) , and development of a low-acid sweet kiwifruit (Wismer et al 2005 ) .…”
Section: Diversifi Cation Of Fruit Typesmentioning
confidence: 99%
“…The extensive literature on how factors such as dry matter content, maturity, storage, firmness when tested, length of storage, and even the temperature of storage of A. deliciosa 'Hayward' fruit can all affect flavor perceptions and preferences in just one cultivar (e.g., Stec et al 1989;Jaeger et al 2003;Marsh et al 2004) indicates the difficulty of making meaningful comparisons of the flavors of fruit from different Actinidia species with the concomitant difficulties in comparing like with unlike. The analytical comparisons that have been made are largely confined to fruit of a restricted number of genotypes of A. chinensis and A. deliciosa: preference mapping indicates that most of the particular genotypes studied of A. chinensis, with sweeter flavors and overtones of black currant, aromatic melon, and candyfloss, are separated by consumers from genotypes of A. deliciosa which are more acid and less "fruity" (Esti et al 1998;Jaeger et al 2003;Wismer et al 2005). However, the sensory profiles did not always segregate according to species, as fruit of one genotype of A. chinensis and of a hybrid between A. chinensis and A. deliciosa had flavor profiles that placed them with fruit of A. deliciosa genotypes.…”
Section: Ripening Indicatorsmentioning
confidence: 99%
“…However, the sensory profiles did not always segregate according to species, as fruit of one genotype of A. chinensis and of a hybrid between A. chinensis and A. deliciosa had flavor profiles that placed them with fruit of A. deliciosa genotypes. The most encouraging conclusion from such sensory studies for kiwifruit breeders is that the success of A. chinensis 'Hort16A' was not that it was preferred by all consumers to the existing A. deliciosa 'Hayward'-it wasn't-but because it had a new and distinct flavor profile that created a new product niche (Wismer et al 2005). The diversity within the rest of the genus thus allows for many new breeding targets.…”
Section: Ripening Indicatorsmentioning
confidence: 99%